Degrees of excellence : a Fatimid treatise on leadership in Islam : a new Arabic edition and English translation of Ahmad b. Ibrāhīm al-Naysābūrī's Kitāb ithbāt al-imāma /: a Fatimid treatise on leadership in Islam : a new Arabic edition and English translation of Ahmad b. Ibrāhīm al-Naysābūrī's Kitāb ithbāt al-imāma. (2009) - Unknown
No abstract available